Prevalence and diversity of parasitic bird lice (Insecta: Psocodea) in northeast Arkansas - Paige J. Brewer; Andrew D. Sweet (International Journal for Parasitology: Parasites and Wildlife, 2023)
Many groups of parasites lack basic information on biodiversity and host associations, which poses challenges for conservation and understanding the ecological relationships between hosts and their parasites. This gap in knowledge is particularly relevant for parasitic species with obscure lifestyles. Ectoparasitc bird lice (Insecta: Psocodea: Phthiraptera) are a group of parasites that has received a relatively substantial research focus, yet patterns of bird-louse relationships and louse diversity remain understudied in many geographic regions, including in parts of the southeastern United States. In this study, we assessed the diversity, prevalence, abundance, and intensity of lice from live and salvaged birds in northeastern Arkansas. We also focused on the frequency of co-occurrence of lice and symbiotic feather mites. Finally, we used nuclear and mitochondrial genes to assess the phylogenic relationships among the most common genera of lice in our sample. We found a total louse prevalence of 10.57% with the highest prevalence on the Passeriformes families Turdidae, Passerellidae, and Parulidae. We also found the louse genera Myrsidea and Brueelia to be the most prevalent and abundant in our sample. Additionally, we reported several novel associations among well-studied bird species. We also found that louse phylogenic patterns tend to reflect host taxonomy and/or ecology. Overall, our results provide important insight into the biodiversity, community structure, and host interactions of parasitic lice from North American birds.